Compound urban heat risk revealed by co-location of social vulnerability and elevated temperatures in London, UK: A spatial analysis - Emma Roberts; Ting Sun; Mark Pelling (Sustainable Cities and Society, 2025)

Normative future visioning for city resilience and development - Mark Pelling; Thaisa Comelli; Marco Cordova; Sibel Kalaycioğlu; Jonathan Menoscal; Rachana Upadhyaya; Matthias Garschagen (Climate and Development, 2024)

COVID-19 Interventions in an informal settlement: A spatial analysis of accessibility in Kibera, Kenya - John Amin Drummond; Bruce D. Malamud; Joe Mulligan; Vera Bukachi; Manshur Talib; Amos Wandera; Mark Pelling; Faith E. Taylor (Journal of Transport Geography, 2023)

Transformative adaptation through nature-based solutions: a comparative case study analysis in China, Italy, and Germany - Anna Scolobig; JoAnne Linnerooth-Bayer; Mark Pelling; Juliette G. C. Martin; Teresa M. Deubelli; Wei Liu; Amy Oen (Regional Environmental Change, 2023)
This paper explores how claims for transformative adaptation toward more equitable and sustainable societies can be assessed. We build on a theoretical framework describing transformative adaptation as it manifests across four core elements of the public-sector adaptation lifecycle: vision, planning, institutional frameworks, and interventions. For each element, we identify characteristics that can help track adaptation as transformative. Our purpose is to identify how governance systems can constrain or support transformative choices and thus enable targeted interventions. We demonstrate and test the usefulness of the framework with reference to three government-led adaptation projects of nature-based solutions (NBS): river restoration (Germany), forest conservation (China), and landslide risk reduction (Italy). Building on a desktop study and open-ended interviews, our analysis adds evidence to the view that transformation is not an abrupt system change, but a dynamic complex process that evolves over time. While each of the NBS cases fails to fulfill all the transformation characteristics, there are important transformative elements in their visions, planning, and interventions. There is a deficit, however, in the transformation of institutional frameworks. The cases show institutional commonalities in multi-scale and cross-sectoral (polycentric) collaboration as well as innovative processes for inclusive stakeholder engagement; yet, these arrangements are ad hoc, short-term, dependent on local champions, and lacking the permanency needed for upscaling. For the public sector, this result highlights the potential for establishing cross-competing priorities among agencies, cross-sectoral formal mechanisms, new dedicated institutions, and programmatic and regulatory mainstreaming.

A climate resilience research renewal agenda: learning lessons from the COVID-19 pandemic for urban climate resilience - Mark Pelling; Winston T. L. Chow; Eric Chu; Richard Dawson; David Dodman; Arabella Fraser; Bronwyn Hayward; Luna Khirfan; Timon McPhearson; Anjal Prakash; Gina Ziervogel (Climate and Development, 2022)

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

Beyond Technical Fixes: climate solutions and the great derangement - Andrea Joslyn Nightingale; Siri Eriksen; Marcus Taylor; Timothy Forsyth; Mark Pelling; Andrew Newsham; Emily Boyd; Katrina Brown; Blane Harvey; Lindsey Jones; Rachel Bezner Kerr; Lyla Mehta; et al. (Climate and Development, 2020)

Climate change-related loss and damage: translating the global policy agenda for national policy processes - Erin Roberts; Mark Pelling (Climate and Development, 2018)

A globally deployable strategy for co-development of adaptation preferences to sea-level rise: the public participation case of Santos, Brazil - Jose A. Marengo; Luci H. Nunes; Celia R. G. Souza; Joseph Harari; Frank Muller-Karger; Roberto Greco; Eduardo K. Hosokawa; Ernesto K. Tabuchi; Samuel B. Merrill; Catherine J. Reynolds; Mark Pelling; Lincoln M. Alves; et al. (Natural Hazards, 2017)

The co-production of risk from a natural hazards perspective: science and policy interaction for landslide risk management in Italy - Anna Scolobig; Mark Pelling (Natural Hazards, 2016)

Adaptation and transformation - Mark Pelling; Karen O’Brien; David Matyas (Climatic Change, 2015)

Associations between elevated atmospheric temperature and human mortality: a critical review of the literature - Simon N. Gosling; Jason A. Lowe; Glenn R. McGregor; Mark Pelling; Bruce D. Malamud (Climatic Change, 2009)